The Optimum Powder Loading of Different Binder Ratio Between HDPE and RWL as Binder in Metal Injection Molding - Zamri, Muhamad Faiz Zamri; Azriszul Mohd Amin, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Metal Injection Molding (MIM) is an advanced manufacturing process that enables the production of intricate and complex parts by mixing metal, ceramic, or cermet powders with binders such as polymers, wax, and surfactants. Adjusting the binder ratio can control the viscosity and rheological behavior of the feedstock, enabling it to flow properly into the mold cavities and achieve the desired shape.This study is focused on different binder ratio of HDPE and RWL in oder to find the optimum powder loading. Different powder loading of aluminium also being used here to determine the possibility of the best binder formulation selected could be optimised for optimal powder loading based on density analysis. Two binder formulations of HDPE and RWL being selected here are 60/40, 50/50 and 40/60 accordingly with the powder loading 80% to 90% for each binder formulation. The amount of metal powder combined with a binder system to create a feedstock for the MIM process is referred to as the powder loading. This experiment is carried out by measure the weight of powder loading and the binder component before it mixing process. Once the feedstock done in the mixing process, the come out with a dough shape and it goes to crusher process to make it look like a small pallet. Density test is done using mettler tolendo device to measure the homogieneity for each of the feedstock that has been made. From the result obtain from the test we can find the optimum powder loading for each binder ratio.The analysis will be based on density measurement. Result from the analysis conducted shows that the volumetric powder loading of 88% with binder volumetric of 50% for HDPE and 50% for RWL contributes significant stability and suitability for optimum powder loading.